Strengthening Future Maritime Transportation Management Through Cognitive Flexibility and Entrepreneurial Mindset Among Generation Z Maritime Students - Hasnur, Juliandri; Yatno, Langandriansyah Dwi (Balai Besar Riset Sosial Ekonomi Kelautan dan Perikanan, 2025)
This study analyzes how digital self-efficacy and social media algorithms influence the development of cognitive flexibility and entrepreneurial mindset among Generation Z maritime students, while identifying policy strategies to integrate these factors into maritime education. Using a quantitative approach with survey data from 209 active students analyzed through Partial Least Square-Structural Equation Modeling (PLS-SEM), the results reveal that digital self-efficacy and social media algorithms significantly influence entrepreneurial mindset and directly affect cognitive flexibility. However, cognitive flexibility does not serve as a mediator between the two independent variables and entrepreneurial mindset. These findings indicate that confidence in digital abilities and exposure to algorithm-driven content are key determinants shaping entrepreneurial thinking among maritime students, whereas the rigid and discipline-oriented nature of maritime education limits the development of adaptive and reflective cognitive skills. The study provides theoretical and practical contributions to understanding the psychological and digital dynamics influencing entrepreneurial readiness in the maritime field. Policy implications highlight the need for maritime higher education institutions and government agencies to strategically leverage social media algorithms and enhance digital self-efficacy through curriculum reform, experiential learning, and digital incubation programs. Aligning these initiatives with Indonesia’s national maritime vision (Visi Poros Maritim Dunia) can foster a new generation of maritime graduates who are not only digitally competent and innovative but also capable of becoming job creators rather than job seekers, contributing to sustainable maritime economic transformation.